India, Pakistan Dispute over the Kashmir Issue and the Current Situation after Articles 370 and 35A - Farooq, Muhammad Sabil; Feroze, Nazia; Cheng, Tongshun (University of Wah Journal of Social Sciences, 2022)
The potential reason for South Asian instability and hostile action is the unresolved nature of the Kashmir dispute between India and Pakistan. In the past, it led to two major wars and several attempted events. Since the early 1990s, India and Pakistan have existed in an "Acting War" on Kashmir. Pakistan has been questioning India’s efforts to strengthen its control over Kashmir through force, and Pakistan supports the Kashmiri’s quest for self-determination in accordance with the UN Resolutions. Prime Minister Modi’s decision to abolish Articles 370 and 35A of the “Indian Constitution” that gave Kashmir a special status has caused controversy throughout the political arena. This paper analyzes the origin of the dispute and its impact on bilateral relations between India and Pakistan after the revocation of Articles 370 and 35A. This study is important because there will be greater realization in India and Pakistan that they need to settle the Kashmir dispute for their wellbeing and that of the region. This study proposes that India and Pakistan need to engage in composite bilateral talks on all important issues. Recurrent tension over Kashmir will undercut any initiative to bring stability to South Asia as well as perpetuate the risk of a nuclear war.